2016
DOI: 10.1016/j.molcel.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Dependent Turnover of MYC Antagonizes MYC/PAF1C Complex Accumulation to Drive Transcriptional Elongation

Abstract: MYC is an unstable protein, and its turnover is controlled by the ubiquitin system. Ubiquitination enhances MYC-dependent transactivation, but the underlying mechanism remains unresolved. Here we show that MYC proteasomal turnover is dispensable for loading of RNA polymerase II (RNAPII). In contrast, MYC turnover is essential for recruitment of TRRAP, histone acetylation, and binding of BRD4 and P-TEFb to target promoters, leading to phosphorylation of RNAPII and transcriptional elongation. In the absence of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 32 publications
8
110
0
Order By: Relevance
“…Alternatively, recruitment may be more indirect; for example, one of the best validated effector functions of C-MYC is the interaction of MYCBoxII with the TRRAP protein, a scaffold of the NuA4 histone acetylase complex, which has multiple roles in gene expression and in maintaining genome stability (134). C-MYC-induced histone acetylation in turn can recruit p-TEFB via the BRD4 protein (135). Intriguingly, NuA4 has recently been implicated in elongation by RNAPII (136), suggesting that recruitment of NuA4 to core promoters may contribute to MYC-dependent pauserelease.…”
Section: N-myc-dependent Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, recruitment may be more indirect; for example, one of the best validated effector functions of C-MYC is the interaction of MYCBoxII with the TRRAP protein, a scaffold of the NuA4 histone acetylase complex, which has multiple roles in gene expression and in maintaining genome stability (134). C-MYC-induced histone acetylation in turn can recruit p-TEFB via the BRD4 protein (135). Intriguingly, NuA4 has recently been implicated in elongation by RNAPII (136), suggesting that recruitment of NuA4 to core promoters may contribute to MYC-dependent pauserelease.…”
Section: N-myc-dependent Transcriptionmentioning
confidence: 99%
“…The efficacy of targeting BRD4 in targeting N-MYCdriven tumors may also be due to a role of BRD4 in MYCdriven transcription, as BRD4 can be recruited by MYC proteins to core promoters (135). Although BRD4 has kinase activity itself, it is best known for its role in recruiting p-TEFB and CDK9 to core promoters.…”
Section: Targeting N-myc Transcriptional Functionmentioning
confidence: 99%
“…It was recently shown that the proteasomal turnover of c-MYC is required for full activity. Lysine-mutated c-MYC failed to induce tumorigenesis as inhibitory complexes could not be removed during target gene activation (58), whereas other TFs are independent of ongoing degradation for their transcriptional activity (60). Surprisingly, EWS-FLI1 induced distinct behavior in three subgroups of target genes.…”
Section: Ews-fli1 Degradation Is Mediated By One Lysine Residuementioning
confidence: 98%
“…Most interestingly, the activity of TFs can be influenced by their own turnover as shown for estrogen receptor ␣ or c-MYC (58,59). It was recently shown that the proteasomal turnover of c-MYC is required for full activity.…”
Section: Ews-fli1 Degradation Is Mediated By One Lysine Residuementioning
confidence: 99%
“…1 MYC binds with the highest affinity to specific DNA sequences, called E-boxes (CACGTG), as a heterodimeric complex with its partner protein MAX, leading to transactivation of its target genes by recruitment of several cofactors, such as TRRAP and associated histone acetyltransferases. 2,3 Given MYC's large number of binding sites and its many target genes, it has been very difficult to assign specific target genes to MYC's oncogenic role, even though it is clear that high MYC activity is predictive in terms of prognosis. 4 Consequently, high MYC activity typically leads to a poor survival prognosis in a multitude of tumor entities.…”
Section: Introductionmentioning
confidence: 99%